Ganoderma lucidum polysaccharide ameliorates cholesterol gallstone formation by modulating cholesterol and bile acid metabolism in an FXR-dependent manner - Dan Huang; Shuang Shen; Qian Zhuang; Xin Ye; Yueqin Qian; Zhixia Dong; Xinjian Wan (BMC, 2024)
Abstract Background Cholesterol gallstone (CG) disease is a worldwide common disease characterized by cholesterol supersaturation in gallbladder bile. Ganoderma lucidum polysaccharide (GLP) has been shown to possess various beneficial effects against metabolic disorders. However, the role and underlying mechanism of GLP in CG formation are still unknown. This study aimed to determine the role of GLP in ameliorating lithogenic diet (LD)-induced CG formation. Methods Mice were fed either a normal chow diet, a LD, or LD supplemented with GLP. Real-time quantitative polymerase chain reaction (RT-qPCR) and western blotting were used to detect the expression of genes involved in cholesterol and bile acid (BA) metabolism. The BA concentrations in the ileum were quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The microbiota in cecal contents were characterized using 16S ribosomal RNA (16S rRNA) gene sequencing. Results GLP effectively alleviated CG formation induced by LD. Specifically, GLP reduced the total cholesterol (TC) levels, increased the total BA levels, and decreased the cholesterol saturation index (CSI) in gallbladder bile. The protective effect of GLP was attributed to the inhibition of farnesoid X receptor (FXR) signaling, increased hepatic BA synthesis and decreased hepatic cholesterol synthesis and secretion. GLP also altered the BA composition in the ileum, reducing FXR-agonistic BAs and increasing FXR-antagonistic BAs, which may contribute to the inhibition of intestinal FXR signaling. Additionally, GLP improved dysbiosis of the intestinal flora and reduced the serum levels of hydrogen sulfide (H2S), a bacterial metabolite that can induce hepatic FXR, thereby inhibiting hepatic FXR signaling. Moreover, the protective effect of GLP against CG formation could be reversed by both the global and gut-restricted FXR agonists. Conclusions Taken together, GLP ameliorates CG formation by regulating cholesterol and BA metabolism in an FXR-dependent manner. Our study demonstrates that GLP may be a potential strategy for the prevention against CG disease.